2007
DOI: 10.1103/physrevb.75.052103
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Jahn-Teller distortion inLaMnO3under pressure: An x-ray absorption study

Abstract: The local environment of manganese atoms in LaMnO3 under pressure up to 15.3 GPa has been studied by x-ray absorption spectroscopy. For pressures below 8 GPa, no change is detected within the MnO6 octahedra. Above this pressure a continuous reduction of the long Mn-O distance takes place, however the octahedral distortion persists over the whole pressure range. At 15.3 GPa the average Jahn-Teller splitting of the distances is reduced by about one third, indicating that a total removal of the local Jahn-Teller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
33
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
9
33
2
Order By: Relevance
“…[1][2][3][4] As a result, there have been many experimental [5][6][7][8] and theoretical [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] studies of the end-member compound LaMnO 3 (LaMnO 3 ). The observed sequence of phases with decreasing temperature is as follows: 8,26 At very high temperature (above 1010 K), LaMnO 3 has a rhombohedral R3c structure, produced by rotation of the oxygen octahedron network of the ideal perovskite structure.…”
mentioning
confidence: 99%
“…[1][2][3][4] As a result, there have been many experimental [5][6][7][8] and theoretical [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] studies of the end-member compound LaMnO 3 (LaMnO 3 ). The observed sequence of phases with decreasing temperature is as follows: 8,26 At very high temperature (above 1010 K), LaMnO 3 has a rhombohedral R3c structure, produced by rotation of the oxygen octahedron network of the ideal perovskite structure.…”
mentioning
confidence: 99%
“…Other authors have reported the persistence of the Jahn-Teller distortion over the entire stability range of the insulating phase of LaMnO 3 , suggesting a non classical Mott insulator. 3,6 No other orthorhombic manganite has attracted such an attention, although we note the pressure investigation of structural properties of the magnetoelectric manganites TbMnO 3 and DyMnO 3 or BiMnO 3 , or more complex solid solutions. [9][10][11] To the best of our knowledge, manganites have not yet been investigated in the very high-pressure regime around 50 GPa, despite promising studies on similar orthoferrites or BiFeO 3 , which have revealed intriguing insulator-to-metal or structural transitions in a similar pressure range.…”
mentioning
confidence: 99%
“…A notable exception is the study of the crystal structure, Jahn-Teller distortion, orbital order, and pressureinduced insulator-metallic phase transition in LaMnO 3 , although the driving mechanism still remains controversial. [2][3][4][5][6][7][8] According to the pioneer work by Loa et al 2 , the Jahn-Teller effect and the concomitant orbital ordering are suppressed above 18 GPa. The system retains insulator behavior up to 32 GPa, undergoing a bandwidth driven insulator-metal phase transition.…”
mentioning
confidence: 99%
“…The evolution δE of the edge threshold as a function of the applied pressure (inset fig. 1) is then essentially related to the specific reduction in this long bond 13 . The overall shift of δE = +1.5 eV corresponds to a reduction of 0.15Å in bond length.…”
mentioning
confidence: 99%
“…In between the evolution of the distortion parameter is given by the open diamond shaped symbols in the figure 3. In the precedent XAS study 13 the data were limited in pressure and quality. By extrapolating the evolution of the JT distortion up to 30 GPa we guessed that the distortion could disappear.…”
mentioning
confidence: 99%